Z problemów niemieckiego osadnictwa rolnego w okolicach Łodzi w początkach XIX wieku. Obrót ziemią - Woźniak, Krzysztof Paweł (Acta Universitatis Lodziensis. Folia Historica, 1995)
This issue was discussed on the examples of two administrative districts of Brzeziny and Łęczyca in 1808-1818. This area was characterized by a great number of colonies inhabited by the population of German origin. The analysis of trade with land was made on the basis of notarial acts. Considering the way of transferring the right o f land property a majority i.e. 92% of 150 studied contracts were transactions o f purchase and sale. Other transactions dealt with exchange o f grounds, division of colonies and granting of the land. The studied phenomenon was characterized by great dynamics. The circle of contracting parties was limited only to colonists’ environment. The representatives of other social groups were represented only occasionally. Also the area, which the contracting parties came from, was limited comprising villages situated within a radius of 35 km. However, inside particular colonies a great boom took place. Frequent changes of land ownership which were the result of looking for better conditions for farming management did not foster the moment of economic stabilization. These conclusions shake the argument, spread by the German historians, about the economic power and big stabilization of German settlers’ colonies in the region of the future Lodz industrial district.